Памятники культуры ранней бронзы на территории Иордании - Аль-Наджар, Мухаммед
Al-Nadjar, Mohammed; Monuments of the Early Bronze Age in Jordan; 2 (engl. Résumé; Frage des Beginns der Bronzezeit in Palästina).